Comparison of Pulse Thermography (PT) and Step Heating (SH) Thermography in Non-Destructive Testing of Unidirectional GFRP Composites - Kamińska Paulina; Ziemkiewcz Jarosław; Synaszko Piotr; Dragan Krzysztof (Fatigue of Aircraft Structures, 2019)
This paper presents two techniques of active thermography i.e. the pulsed thermography technique and the step heating technique. The aim of this article is to compare these two techniques and present the possibilities, advantages and limitations of their use in the context of non-destructive testing of composite materials. The experimental section presents the results of tests carried out on samples of the polymer composites reinforced with glass fiber.